Puritan Islam: the geoexpansion of the Muslim world - Vann, Barry A. (Prometheus Books, 2011)
Qur'anic geotheology and other perspectives of Islam -- An emerging Muslim world -- Puritans' view of self and community -- Puritans' perception of unbelievers -- The sanctity of Allah's world -- Toward a theocratic nation -- American's Islam's two communities -- The incommensurability of liberalism and puritan Islam -- Puritans' perceptions of the State of Israel -- Future geographies of Islam